Mortality from oral and oropharyngeal cancer in Brazil: impact of the National Oral Health Policy - Amanda Ramos da Cunha; Taiane Schaedler Prass; Fernando Neves Hugo (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2019)
Abstract: The objective was to investigate if there is an association between the mortality rates due to oral and oropharyngeal cancer in Brazil and the expansion of access to public primary and specialized dental care services that resulted from the implementation of the National Oral Health Policy, between 2000 and 2013. The mortality data were obtained from the records of the Mortality Information System and the exposure variables were obtained from databases of the Brazilian Ministry of Health and the Brazilian Institute of Geography and Statistics. The main exposures investigated were "coverage of primary dental care" and "number of specialized dental care centers". Additional covariates included "Gini index of household income", "average number of years of study", "proportion of unemployed people" and "proportion of smokers". For the statistical analysis, a random coefficient model was used. There was a statistically significant association between the mortality rates by oral and oropharyngeal cancer with coverage by primary dental care and the number of specialized dental care centers with males. This study found that the expansion of the coverage of primary dental care and the number of specialized dental care centers are associated with the reduction of mortality rates due to oral and oropharyngeal cancer in Brazil. There is plausibility for the association found, which needs to be confirmed by implementation studies.